An Evaluation of the Determinants of Remittances: Evidence from Nigeria - Laniran, Temitope; Adeniyi , Daniel (African Human Mobility Review, 2021)
International remittances have grown to become an integral source of finance for development. Existing literature posits that there is an association between remittances and growth in developing countries. Economic growth models highlight the importance of capital accumulation and high level financial flows, the inadequacy of which characterizes developing countries and often explains their fate. It is argued that remittances will provide a panacea to the serious poverty experienced in such developing economies by increasing financial flows and household income, which in turn stimulates consumption, savings, economic growth and ultimately development. The robustness of this relationship is, however, often questioned. Indeed, the propensity of remittances to achieve these aspirations very much hinges on the determining factors motivating the remitters and the magnitude of the remittances. Hence, given the significant flows of remittances to the developing countries, this study attempts an analysis of the determinants of remittances to Nigeria. Key macroeconomic variables with theoretical potentials of influencing the level of remittances received were subjected to econometric model testing using time series data from 1980 to 2013. The results indicate that the level of remittances received is more a function of portfolio motives than other macroeconomic factors.